Reconstruction of Criminal Law to Address Cyber Terrorism in Indonesia - Dwi Nugroho Marsudianto; Herman Bakir (Al-Makki Publisher, 2024)
Cyber terrorism uses information and communication technology to scare individuals or governments. In Indonesia, terrorism-related cyberattacks have increased by 300% in the past year, despite regulations such as the Law on the Eradication of Terrorism and the Law on Electronic Information and Transactions (UU ITE). This legal gap in handling cybercrime requires an effective reconstruction of criminal law. This research aims to analyze the effectiveness of law enforcement against cyber terrorism, identify legal gaps, and provide recommendations for necessary legal reforms. The approach used is normative law, with analysis of the Law on Eradication of Terrorism and ITE Law, as well as case studies to explore challenges in law enforcement. It was found that there are normative gaps in the existing regulations. While the ITE Law and Terrorism Eradication Law provide a legal framework, they do not clearly define cyber terrorism or provide sufficiently strict sanctions. There is a need for regulatory reform to cover aspects of cybercrime. Proposed reforms include a clear definition of cyber terrorism, increased sanctions, and the application of technology in law enforcement. International cooperation and public awareness are also important to create a safe environment. To improve law enforcement against cyber terrorism in Indonesia, comprehensive law reform is needed. Gaps in the ITE Law and Terrorism Eradication Law should be addressed with clear definitions and stricter sanctions, as well as through the use of technology and international cooperation